Transcription factor c-Myb inhibits breast cancer lung metastasis by suppression of tumor cell seeding - Knopfová, L; Biglieri, E; Volodko, N; Masařík, M; Hermanová, M; Glaus Garzón, J F; Dúcka, M; Kučírková, T; Souček, K; Šmarda, J; Beneš, P; Borsig, L (Oncogene, 2018)
Metastasis accounts for most of cancer-related deaths. Paracrine signaling between tumor cells and the stroma induces changes in the tumor microenvironment required for metastasis. Transcription factor c-Myb was associated with breast cancer (BC) progression but its role in metastasis remains unclear. Here we show that increased c-Myb expression in BC cells inhibits spontaneous lung metastasis through impaired tumor cell extravasation. On contrary, BC cells with increased lung metastatic capacity exhibited low c-Myb levels. We identified a specific inflammatory signature, including Ccl2 chemokine, that was expressed in lung metastatic cells but was suppressed in tumor cells with higher c-Myb levels. Tumor cell-derived Ccl2 expression facilitated lung metastasis and rescued trans-endothelial migration of c-Myb overexpressing cells. Clinical data show that the identified inflammatory signature, together with a MYB expression, predicts lung metastasis relapse in BC patients. These results demonstrate that the c-Myb-regulated transcriptional program in BCs results in a blunted inflammatory response and consequently suppresses lung metastasis.
Keywords: Gene Expression Regulation, Neoplastic; nádorové mikroprostředí; Proto-Oncogene Proteins c-myb; nádory plic; lokální recidiva nádoru; Cell Proliferation; Mice, SCID; Lung Neoplasms; Chemokine CCL2; prognóza; Xenograft Model Antitumor Assays; regulace genové exprese u nádorů; chemokin CCL2; myši inbrední BALB C; nádory prsu; Mice, Inbred BALB C; myši inbrední NOD; xenogenní modely - testy protinádorové aktivity; Neoplasm Recurrence, Local; Animals; protoonkogenní proteiny c-myb; lidé; ženské pohlaví; Breast Neoplasms; Humans; zvířata; myši SCID; myši inbrední C57BL; nádorové buňky kultivované; myši; apoptóza; proliferace buněk; Mice, Inbred C57BL; Prognosis; Tumor Cells, Cultured; Mice; Female; Mice, Inbred NOD; Tumor Microenvironment; Biomarkers, Tumor; nádorové biomarkery; Apoptosis